Integrative Local Wisdom-Based Islamic Education Curriculum for Intercultural Sensitivity Development in Tourism Vocational Schools - Sayuti, Sadip Indra Irawan; Hafizin, Hafizin (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2026)
This study aims to develop an Islamic Education (PAI) curriculum model grounded in Sasak local cultural values to enhance intercultural sensitivity among vocational high school students in the tourism sector within the Mandalika Special Economic Zone, Lombok. The study employs a Research and Development (R&D) approach by adapting the Borg and Gall model into five stages: needs analysis, initial model development, expert validation, limited trials, and field implementation. The research was conducted at Vocational High School (SMKN) 1 Pujut, a Center of Excellence vocational school situated in a multicultural environment with established tourism industry partnerships. Data were collected through interviews, observations, document analysis, and the Intercultural Sensitivity Scale (ISS) administered in pre- and post-tests, and analyzed using a mixed-methods approach. The findings indicate that the integration of Sasak cultural values such as solah, lomboq, rema, into the Islamic Religious Education (Ire) curriculum enhances students’ empathy, respect for diversity, and openness in intercultural interactions. The developed model is found to be valid, contextually relevant, and effective for implementation in multicultural tourism-oriented vocational schools.